МЕТОДОЛОГІЯ УПРАВЛІННЯ ЗМІНАМИ: МОДЕЛЬ ШІНГО - Kashchuk, Kateryna (Zhytomyr Ivan Franko State University, 2024)
The article examines and summarizes information about the work and effectiveness of the model of Japanese scientific engineer Shigeo Shingo (1909–1990) Questions regarding the prerequisites for its emergence, development, and implementation in the management of Japanese enterprises and companies are addressed, as well as the potential application of this model in Ukrainian enterprises. The value system at enterprises is analyzed in the context of the Shingo model and its role in the involvement of employees in the process of transformation of production. The Shingo model is used to analyze the role of employees in the process of transformation of production. In the present circumstances of the transition of Ukrainian enterprises to a highly volatile stage of development, the significance of the subject matter is undeniable. Value orientations and authentic models of employee behavior of developing enterprises become topical in the context of the need to move towards high productivity. It is therefore important to assess the degree of readiness of the economy for the transformation process, its ability to adapt to changes, and its potential speed of introduction of technologies and innovations. In this work, the effective structure of the production transformation process and the individual elements of the transformation are indicated. It is demonstrated the impact of innovative methods and methods of transformation on the speed of growth and development of productivity at enterprises. The material presented in the article encompasses significant aspects of the fundamental essence of the innovative nature of development based on the Shingo model.